The Influence of CAR and ROA on MSME Financing of Sharia Rural Bank in Indonesia - fahri eka oktora; Sulaiman Sulaiman (Economy Deposit Journal (E-DJ), 2022)
The purpose of this study is to investigate the impact of the Capital Adequacy Ratio (CAR) and Return On Assets (ROA) on Islamic People's Financing Banks' MSME Financing in Indonesia. CAR (X1) and ROA (X2) are the independent variables in this study, whereas MSME Financing is the dependent variable (Y). This is a quantitative study that will take place in 2021, from January to December, using secondary data that has already been released. The Islamic People's Financing financial ratio was acquired from the Financial Services Authority's (OJK) statistics report of Islamic banks issued in 2021 utilizing Time series data, and the test of this study was multiple linear regression using Stata 16 as the measuring instrument. Multiple linear regression was employed in this study, and it was chosen based on the model accuracy test and the classical assumption test using normality, heteroscedasticity, and multicollinearity test techniques. The study's findings show that CAR and ROA have a favourable association with MSME funding at the same time. MSME finance will rise with every increase in ROA and CAR. While CAR has a largely favourable association with MSME finance, ROA has a negatively related relationship with MSME financing.